Classroom Management: Glocalized Contexts - Pokharel, Manda; Sharma, Mani Ram (Journal of Social Work and Science Education, 2021)
This research based article discusses on issues and practices of classroom management from the local perspectives. It is based on the context of public school of Nepal. The participant is an EFL teacher of public school in Kathmandu, teaching in middle school and secondary level there. The classroom management practices in the EFL teacher’s classes are seen using classroom observation tool, in her classes of both the levels for a week using qualitative framework. The findings show the traditional practice still dominating the classroom activities. Therefore the article is based on the issues of classroom management being specific to the seating arrangements, discipline, peer work, group work, space, presentation, and time management in the public school where classroom observation has been done.